The New Fire : war, peace, and democracy in the age of AI - Buchanan, Ben; Imbrie, Andrew (Cambridge, Massachusetts: London, England: The Mit Press, 2022)
"Is AI a force for ill or for good? How does it work? This book analyzes the potential of AI in many sectors, including global security"
Introduction -- Part 1. Ignition. Data -- Algorithms -- Compute -- Failure -- Part 2. Fuel. Inventing -- Killing -- Hacking -- Lying -- Part 3. Wildfire. Fear -- Hope.
Keywords: Artificial intelligence